Prefrontal activity during the emotional go/no-go task and computational markers of risk-based decision-making predict future relapse in alcohol use disorder - Sasaki, Jun; Matsubara, Toshio; Chen, Chong; Fujii, Yuko; Fujita, Yoko; Nakamuta, Masako; Nitta, Kumiko; Egashira, Kazuteru; Hashimoto, Takashi; Nakagawa, Shin (Frontiers in Psychiatry, 2023)
Aim: To longitudinally examine if the results of cognitive tasks or brain function during emotional or cognitive tasks can predict relapse in alcohol use disorder. Methods: We selected 41 patients with alcohol use disorder during hospitalization. Functional near-infrared spectroscopy measured the relative change in oxygenated hemoglobin in the frontotemporal areas during an emotional go/no-go task and verbal fluency task. They performed the N-back and risk-based decision-making tasks for determining working memory or risk-based decision-making. The presence of relapse 6 months following discharge was the primary outcome. Results: Twenty-four patients (21 men, three women) remained abstinent, whereas 17 (14 men, three women) relapsed. Compared with the abstinent group, those with relapse displayed significantly decreased activation in the right frontotemporal region during the emotional go/no-go task, significantly shorter reaction time to non-emotional stimuli, and greater risk preference in the risk-based decision-making task. In the abstinent group, we observed a negative correlation between oxygenated hemoglobin and the craving scale. A logistic regression analysis demonstrated that the risk of relapse increased with smaller oxygenated hemoglobin in the right frontotemporal region (odds ratio = 0.161, p=0.013) and with greater gambling thoughts (odds ratio = 7.04, p=0.033). Conclusions: Decreased activation in the right frontotemporal region in response to an emotional stimulus and risk preference could predict relapse in alcohol use disorder.